Intraoperative video recording in otolaryngology for surgical education: evolution and considerations - Hannah L. Brennan; Simon D. Kirby (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Otolaryngology is a surgical speciality well suited for the application of intraoperative video recording as an educational tool considering the number procedures within the speciality that utilize digital technology. Intraoperative recording has been utilized in endoscopic surgeries and in evaluating technique in mastoidectomy, myringotomy and grommet insertion. The impact of intra-operative video recording in otolaryngology education is vast in creating access to surgical videos for preparation outside the operating room to individualized coaching and assessment. The purpose of this project is to highlight the role of intraoperative video recording in otolaryngology training and elucidate the challenges and considerations associated with implementation. Methods Related publications between 1999 to 2022 were reviewed from PubMed and Embase databases utilizing search terms “intraoperative videography,” “video recording surgery,” “otolaryngology,” and “surgical education.” 109 articles were screened independently by HB and SK, by title and abstract then full text review. 28 articles from the original search and 6 from the secondary reference review were included. Results The application of intraoperative video recording is evident in otolaryngology surgeries including endoscopic sinus surgery, laryngeal surgery, and other endoscopic procedures. There have been significant advancements in recording tools, including devices that can capture the surgeon’s perspective. The considerations and challenges identified with utilizing this educational tool were categorized into different themes including ethics/consent, regulation, liability, data, technology, and human resources. Conclusion Intra-operative video recording has been demonstrated to have significant impact within otolaryngology education. It is critical to elucidate the challenges and considerations involved to utilize this educational tool effectively. Future directives will see video-based performance analytics providing comparative metrics to encourage precise coaching of surgical residents.